2017
DOI: 10.1073/pnas.1702014114
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate-like CRYPTOCHROME 2 from monarch regulates circadian transcription via independent repression of CLOCK and BMAL1 activity

Abstract: Circadian repression of CLOCK-BMAL1 by PERIOD and CRYPTOCHROME (CRY) in mammals lies at the core of the circadian timekeeping mechanism. CRY repression of CLOCK-BMAL1 and regulation of circadian period are proposed to rely primarily on competition for binding with coactivators on an α-helix located within the transactivation domain (TAD) of the BMAL1 C terminus. This model has, however, not been tested in vivo. Here, we applied CRISPR/Cas9-mediated mutagenesis in the monarch butterfly (Danaus plexippus), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 48 publications
4
64
0
Order By: Relevance
“…The seasonal plasticity of monarch butterflies trans-generational migratory behaviour, on the other hand, offers opportunities to study the epigenetic basis of migration. With the ability to maintain colonies in the laboratory year-round, a fast generation time and its accessibility to in vivo genetic manipulation (Merlin et al, 2013;Markert et al, 2016;Zhang et al, 2017), the monarch is also uniquely suited to rapidly assess the function of candidate migratory genes (Fig. 3B).…”
Section: The North American Monarch Butterfly Danaus Plexippusmentioning
confidence: 99%
See 1 more Smart Citation
“…The seasonal plasticity of monarch butterflies trans-generational migratory behaviour, on the other hand, offers opportunities to study the epigenetic basis of migration. With the ability to maintain colonies in the laboratory year-round, a fast generation time and its accessibility to in vivo genetic manipulation (Merlin et al, 2013;Markert et al, 2016;Zhang et al, 2017), the monarch is also uniquely suited to rapidly assess the function of candidate migratory genes (Fig. 3B).…”
Section: The North American Monarch Butterfly Danaus Plexippusmentioning
confidence: 99%
“…Brain clocks are, however, most likely involved in the induction of the migratory traits and could impact migratory traits by regulating the transcription of clock genes and clock-controlled genes in this tissue (Hardin and Panda, 2013). With the availability of several clock gene knockouts in monarchs (Merlin et al, 2013;Markert et al, 2016;Zhang et al, 2017), functionally determining whether circadian clocks or clock genes play a role in the migratory switch should now be feasible, at least in this system.…”
Section: Accurate Phenotyping Of Migratory Behaviour Is Keymentioning
confidence: 99%
“…The magnetic response of positive phototaxis we found here is likely to be a result of interactions between the roles of Drosophila -like Cry1 in phototaxis and magnetoreception [1, 3, 4, 40], even though Cry2 may also function in a complex with photoreceptors or downstream in magnetoreception signaling [42]. Moreover, given that Cry2 is a component of the core circadian clock and it is reported that circadian clock is sensitive to changes in magnetic field intensity [11, 43], a Cry2 function as a potential timing mechanism for migration based on GMF intensity might also exist [44].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the secondary pocket in photoreceptive cryptochromes from Arabidopsis and Drosophila (Brautigam et al, 2004;Levy et al, 2013), as well as the evolutionarily related DNA repair enzymes, CPD or (6-4) photolyase (Hitomi et al, 2009;Park et al, 1995), is considerably smaller in volume, where it binds to small molecule cofactors that facilitate light harvesting (Sancar, 2003). The ability of repressor-type cryptochromes to interact with CLOCK PAS-B appears to be deeply rooted in evolution of the metazoan circadian clock, because the vertebrate-like cryptochromes that act as transcriptional repressors in insects (Zhu et al, 2005) like the monarch butterfly also depend to the same extent on multivalent interactions with CLOCK PAS-B and the BMAL1 TAD as they do in mammals (Sato et al, 2006;Xu et al, 2015;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The BMAL1 TAD is the primary driver of transcriptional activation by CLOCK:BMAL1 in mammalian and insect systems with repressor-type cryptochromes; truncation or mutation of the TAD decimates CLOCK:BMAL1 activity and leads to arrhythmicity in vivo (Kiyohara et al, 2006;Park et al, 2015;Zhang et al, 2017). Sequestration of the TAD by repressor-type cryptochromes allows them to compete with coactivators at a highly conserved and overlapping binding motif (Xu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%